2018
DOI: 10.1113/jp276714
|View full text |Cite
|
Sign up to set email alerts
|

Anticipation of food intake induces phosphorylation switch to regulate basolateral amino acid transporter LAT4 (SLC43A2) function

Abstract: Key points Amino acid absorption requires luminal uptake into and subsequent basolateral efflux out of epithelial cells, with the latter step being critical to regulate the intracellular concentration of the amino acids. The basolateral essential neutral amino acid uniporter LAT4 (SLC43A2) has been suggested to drive the net efflux of non‐essential and cationic amino acids via parallel amino acid antiporters by recycling some of their substrates; its deletion has been shown to cause defective postnatal growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 71 publications
7
22
0
Order By: Relevance
“…SLC43A2 has a broader expression profile than SLC43A1, being expressed in the placenta, kidney, leukocytes, and at lower levels in many other tissue types [192]. The localization of this protein to the plasma membrane follows feeding patterns in mice, with increased plasma membrane expression of SLC43A2 occurring cyclically in anticipation of food intake, attesting to a role for SLC43A2 in amino acid absorption [196]. This protein is also required for proper mouse development, with knockout models exhibiting significant growth retardation and low amniotic fluid amino acid levels [197].…”
Section: Slc43mentioning
confidence: 99%
“…SLC43A2 has a broader expression profile than SLC43A1, being expressed in the placenta, kidney, leukocytes, and at lower levels in many other tissue types [192]. The localization of this protein to the plasma membrane follows feeding patterns in mice, with increased plasma membrane expression of SLC43A2 occurring cyclically in anticipation of food intake, attesting to a role for SLC43A2 in amino acid absorption [196]. This protein is also required for proper mouse development, with knockout models exhibiting significant growth retardation and low amniotic fluid amino acid levels [197].…”
Section: Slc43mentioning
confidence: 99%
“…These reports suggest that absorption of peptides in small intestine exhibits diurnal variation via the DBPand PPARα-mediated circadian control of PEPT1 expression. In recent years, time-dependent intestinal absorption of amino acids has been reported (56,57). Jando et al reported that isoleucine absorption is higher in the active phase than in the rest phase, although the protein levels of intestinal amino acid transporter B0AT1 in the rat intestine are not changed between the two time points (57).…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
“…The branched-chain amino acids, such as leucine, valine, and isoleucine, are absorbed via LAT4 (SLC43A2), a basolateral neutral amino acid transporter (58). LAT4 phosphorylation at Ser274 is higher at the beginning of the rest phase than at the beginning of the active phase in mice (56). LAT4 shows high activity under dephosphorylated condition, suggesting that post-translational modulation such as phosphorylation could be involved in the time-dependent amino acid absorption.…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
“…We can nevertheless not exclude a compensatory change at the level of other transporters or even at the level of the tested ones, if occurring by post‐transcriptional modifications, such as LAT4 that itself was shown to undergo post‐translational regulation in the context of food anticipation, specifically by serine (de)phosphorylation (Oparija et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The primary antibodies used were: rabbit anti-LAT4, guinea pig anti-B 0 AT1 (Guetg et al 2015), rabbit anti-LAT2 (Vilches et al 2018) and mouse anti-ß actin (Oparija et al 2019) as described previously. The secondary antibodies used include: Alexa Fluor 594 anti-rabbit (catalogue no.…”
Section: Antibodiesmentioning
confidence: 99%